ASSESSMENT OF CARDIOVASCULAR RISK IN PATIENTS WITH TYPE 2 DIABETES MELLITUS AND NONALCOHOLIC STEATOHEPATITIS - Albai, Oana; Timar, Bogdan; Timar, Romulus (European Scientific Journal, ESJ, 2013)
The nonalcoholic steatohepatitis is the leading cause of hepatic morbidity and mortality, the patients being at very high risk of developing cirrhosis, liver failure and hepatocellular carcinoma. Its growing incidence and prevalence in patients with diabetes mellitus and metabolic syndrome indicates that these entities have at least one common pathogenic mechanism, where the main factors are visceral obesity and insulin resistance. Purpose: The purpose of this study was to explore the prevalence of nonalcoholic steatohepatitis in a group of patients with type 2 DM from the Timis County, as well as NASH relationships with other cardiovascular risk factors, such as obesity, dyslipidemia and arterial hypertension. Material and method: The study included 310 patients with type 2 DM, 123 men (39.7%) and 187 women (60.3%) with mean age 59.6 Â± 8.1 (39-79) years, treated within the Antidiabetes Center Timisoara between March-December 2012. Results and discussions: The nonalcoholic steatohepatitis was diagnosed in 208 patients (71.5%), 90 men (78.9%) and 118 women (66.6%), its prevalence being higher in males. Analyzing the metabolic syndrome components, we found that all examined parameters were statistically significantly higher in patients with nonalcoholic steatohepatitis, showing an extremely high cardiovascular risk in this category of patients. Conclusions: The therapeutic strategy in nonalcoholic steatohepatitis involves the decrease of visceral fat and the improvement of insulin resistance.